2013
DOI: 10.1111/all.12141
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergies: is the farming environment (still) protective in Poland? The GABRIEL Advanced Studies

Abstract: While farming in Poland differed from that in the Alpine areas as did the exposure-response associations, we found in communities engaged in small-scale, mixed farming, there was a protective farming effect against objective measures of atopy potentially related to contact with grain or associated farm activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…Observations linking exposure to green environments and agriculture to protection from illness were made as early as the 19th century by Blackley who noticed that hay fever was rare among farmers (78). This observation has now been confirmed in many countries using rigorous epidemiological methods (54,79). Moreover exposure to farms also protects from juvenile forms of inflammatory bowel disease (80).…”
Section: Natural Environment and Immunoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations linking exposure to green environments and agriculture to protection from illness were made as early as the 19th century by Blackley who noticed that hay fever was rare among farmers (78). This observation has now been confirmed in many countries using rigorous epidemiological methods (54,79). Moreover exposure to farms also protects from juvenile forms of inflammatory bowel disease (80).…”
Section: Natural Environment and Immunoregulationmentioning
confidence: 99%
“…2). This urban increase is true for allergies (53,54), inflammatory bowel disease (55), and for autoimmune diseases such as MS (56)(57)(58). These urban-rural differences are equally obvious in psychiatric disorders (59).…”
Section: Progressive Loss Of Microbial Inputsmentioning
confidence: 99%
“…[8] Further, numerous studies report an inverse correlation for atopy for children who were raised on a farm versus nonfarm children, suggesting that farming is protective of atopy. [911] Interestingly, asthma and farming exposures do not consistently follow a similar trend, which is likely explained by the multi-factorial clinical phenotypes of asthma and the heterogeneity of farming exposures. [10]…”
Section: Farming Exposures In Children Is Protective: the Evidencementioning
confidence: 99%
“…The GABRIELA study findings to date have also highlighted other factors which may be important in understanding the correlations with atopy, asthma, and degree of protection. [9, 11, 14, 17, 18] The GABRIELA study group has found that the protective nature of farm exposures in Europe is not universal. A subset of Polish farm children within the GABRIELA studies did not appear to gain as much protection against the development of asthma compared to those children who lived on a farm in the Alpine areas.…”
Section: Farming Exposures In Children Is Protective: the Evidencementioning
confidence: 99%
“…This comprised both obtaining further information from the parents and a qualified nurse taking a blood sample and nasal swab and performing a prick skin test on school grounds. These tests were conducted on a random selection of children from the group of 9,677 [26,27]. …”
Section: Discussionmentioning
confidence: 99%